2020
DOI: 10.1172/jci141054
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral CD4+ T cell subsets and antibody response in COVID-19 convalescent individuals

Abstract: Background: Marked progress is achieved in understanding the physiopathology of COVID-19 that caused global pandemics. However, CD4 + T cell population that is critical for antibody response in COVID-19 is poorly understood. Methods: In this study, we provided a comprehensive analysis of peripheral CD4 + T cells of 13 COVID-19 convalescent patients, as defined as confirmed free of SARS-CoV-2 for 2-4 weeks, using flow cytometry, magnetic chemiluminescence enzyme antibody immunoassay and correlated the data with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
166
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(186 citation statements)
references
References 71 publications
14
166
3
3
Order By: Relevance
“…Odak, I. et al [15] have also shown that central memory CD4+ cells were dominated among CD4+ T lymphocytes, while percentages of CD4+ effector cells were reduced. Gong F. et al [34] also observed that SARS-CoV-2-specific CD4+ T cells in blood were typically of central memory phenotype. Sekine, T. et al [35] have presented that in patients with acute-phase of COVID-19 infection specific T cells displayed a highly activated cytotoxic phenotype, whereas in convalescent-phase T cells were polyfunctional and displayed a memory phenotype, the same in asymptomatic individuals and mild patients.…”
Section: T Cells Maturation In Covid-19 Patients: Role Of Central Memmentioning
confidence: 91%
See 1 more Smart Citation
“…Odak, I. et al [15] have also shown that central memory CD4+ cells were dominated among CD4+ T lymphocytes, while percentages of CD4+ effector cells were reduced. Gong F. et al [34] also observed that SARS-CoV-2-specific CD4+ T cells in blood were typically of central memory phenotype. Sekine, T. et al [35] have presented that in patients with acute-phase of COVID-19 infection specific T cells displayed a highly activated cytotoxic phenotype, whereas in convalescent-phase T cells were polyfunctional and displayed a memory phenotype, the same in asymptomatic individuals and mild patients.…”
Section: T Cells Maturation In Covid-19 Patients: Role Of Central Memmentioning
confidence: 91%
“…Odak, I. et al [15] similar to our observation have shown that patients in mild course had higher proportion of CD8+ effector T cells than healthy control. Gong F. et al [34] have also shown that SARS-CoV-2-specific CD8+ T-cells typically had a more effector phenotype. Westmeier, J. et al [36] found that SARS-CoV-2 infection induced a cytotoxic response of CD8+ T cells, characterized by the simultaneous production of granzyme A and B as well as perforin.…”
Section: T Cells Maturation In Covid-19 Patients: Role Of Central Memmentioning
confidence: 92%
“…For example, Th2-cTfh cells have been associated with the acquisition of broadly neutralizing antibodies against HIV, 10 while Th1-cTfh cells are linked to the induction of antibodies following viral infection and vaccination, including influenza, HIV, and severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). [16][17][18][19] cTfh cell activation during P. falciparum infection in humans has only been investigated in a single study of Malian children. 20 This study reported that during P. falciparum malaria, cTfh cell activation was restricted to Th1-cTfh cells, and activation was not correlated with anti-malarial immunoglobulin G (IgG) responses.…”
Section: Introductionmentioning
confidence: 99%
“…Patient recovered from acute COVID-19 also have CD127 + effector and central memory CD4 + T-cells and CD57 + differentiated memory CD8 + T-cells and their DCs, including CD1c + , CD11c + , and pDCs also increase [199] . However, convalescent COVID-19 HDs show 2 fold decrease in the frequency of central memory CD4 + T cells and 1.5 fold in CD4 + effector memory T cells [294] . There is a difference in the overall frequency of circulating T FHs between SARS-CoV2 unexposed HDs and convalescent COVID-19 HDs.…”
Section: Immune Status In Covid-19 Convalescent Patientsmentioning
confidence: 91%
“…The patients recovered from COVID-19 have high amount of spike (S)-specific Abs and patients died due to COVID-19 show high level of nucleocapsid (N)-specific Abs that has been validated in a large cohort [293] . Comparable naïve CD4 + T cells are present in HDs and convalescent COVID-19 HDs [294] . Patient recovered from acute COVID-19 also have CD127 + effector and central memory CD4 + T-cells and CD57 + differentiated memory CD8 + T-cells and their DCs, including CD1c + , CD11c + , and pDCs also increase [199] .…”
Section: Immune Status In Covid-19 Convalescent Patientsmentioning
confidence: 95%